An effective field screening method for flood tolerance in soybean. (11th July 2017) - Wu, Chengjun; Zeng, Ailan; Chen, Pengyin; Florez‐Palacios, Liliana; Hummer, Wade; Mokua, Jane; Klepadlo, Mariola; Yan, Long; MA, Qibin; Cheng, Yanbo
Abstract: Flooding is an abiotic stress that causes considerable reductions in crop growth and yield worldwide. Soybean ( Glycine max [L.] Merr.) cultivars are generally sensitive to flooding stress. The objective of this study was to develop an effective flooding tolerance screening method in the field. A total of 40 soybean genotypes were evaluated for flooding tolerance at V5 and R1 growth stages. At each stage, genotypes were exposed to different durations of flooding stress (3, 6, 9, 12 and 15 days). Plant foliar damage score (FDS) and plant survival rate (PSR) were used as the indicators of flooding tolerance. Soybeans were more sensitive to flooding at R1 growth stage than V5 growth stage. Length of flooding duration accounted for the variance of FDS and PSR. Soybean genotypes exposed to a 3‐day flooding in either V5 or R1 growth stage, did not show obvious foliar damage, while genotypes exposed to a 12‐ or 15‐day flooding showed significant foliar damage and plant death. The optimum flooding duration to screen for flooding tolerance in the field was determined to be 9 and 6 days for V5 and R1 growth stages, respectively, as distinguishable responses to flooding allowed genotypes to be classified as either being flooding tolerant or flooding sensitive. High correlation between FDS and PSR (.99, p  < .0001) was observed. Similarly, FDS and PSR were highly correlated with grain yield (.95 and .95, p  < .0001). The field screening method for flooding tolerance developed in our study will be favourable for selection of soybean flooding‐tolerant germplasm.